2022
DOI: 10.1002/smll.202201826
|View full text |Cite
|
Sign up to set email alerts
|

Color‐Tunable Fluorescent Hierarchical Nanoassemblies with Concentration‐Encoded Emission

Abstract: Cephalopods possess a dynamic coloration behavior to change their iridescence due to the concentration‐induced optical properties of chromatophores and hierarchical assembly of reflectin. However, cephalopods rarely have iridescence in the darkfield. It would be interesting to develop color‐tunable fluorescent hierarchical nanoassemblies with concentration‐encoded emission. Herein, to construct the bioavailable fluorophore with dynamic coloration properties, a histidine‐rich peptide is designed, which can self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…The diphenylalanine motif here, which coincides with the core recognition motif of Alzheimer’s β-amyloid polypeptide, was designed to increase the amphiphilicity and assembly properties of the tetrapeptide . Histidine was assigned at the terminal, which may facilitate the production of multicolor emissions as we previously studied . To conclude, we intend to utilize the assembly induced emissions of reducedand oxidizedtetrapeptide to produce ratiometric emissions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diphenylalanine motif here, which coincides with the core recognition motif of Alzheimer’s β-amyloid polypeptide, was designed to increase the amphiphilicity and assembly properties of the tetrapeptide . Histidine was assigned at the terminal, which may facilitate the production of multicolor emissions as we previously studied . To conclude, we intend to utilize the assembly induced emissions of reducedand oxidizedtetrapeptide to produce ratiometric emissions.…”
Section: Resultsmentioning
confidence: 99%
“…We noticed that compared to the CD spectra of the thiol from, the proportion of the antiparallel β-sheets of the disulfide form of the tetrapeptide increased obviously. As the peptide nanostructure is usually amorphous making it challenging to get experimental crystal data under physiological conditions, , we then performed coarse-grained molecular dynamics (CG-MD) simulations of the roGFP2 mimetic tetrapeptide as well as the oxidic disulfide form of the tetrapeptide to gain insights into the structural basis of ratiometric fluorescence at a molecular level. The CG-MD results revealed that both the thiol and the disulfide form of the tetrapeptide can self-assemble into clusters and the clusters further merge into the nanosphere within 1000 ns (Figure c and Supplementary Figures S14 and S15).…”
Section: Resultsmentioning
confidence: 99%
“…Molecular dynamics simulations were performed as we previously reported . In detail, the coarse-grained molecular dynamics (CG-MD) simulations were performed using GROMACS 2019.6 software.…”
Section: Experimental Section/methodsmentioning
confidence: 99%
“…Herein, we design a ferrocene-modified histidine dipeptide ( f- HH dipeptide) as the histidine residue can construct color-tunable peptide nanostructures, as shown in our previous study. , The f- HH dipeptide has a ratiometric fluorescence, of which the value was linear with the peptide concentration with a correlation range of three orders of magnitude. We expand this unique concentration-encoded emission toward a quantitative assessment of its intracellular distribution as well as the biocompatible ratiometric biosensors .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation